LEARNING STYLES AMONG TERTIARY LEVEL STUDENTS: A CASE STUDY ON PRIVATE COLLEGES IN MALAYSIA - Mohd Bakri Abu Bakar, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The aim of the study is to find out the preference of learning styles among tertiary level students by stream programme and gender. The scope of the study is to look at private colleges in order to see the different culture and atmosphere of students in applying and practicing their learning styles against what the public universities have offered. There are 100 respondents from two (2) private colleges in Kedah and Kelantan have been selected which enrolling in the field of arts and sciences programme. A set of a questionnaire consisting of three (3) sections of learning styles (VAK) adopted by O’Brien (1985) is distributed to all respondents after the class session. The results have concretely shown that most of the respondents regardless of stream programmes prefer visual learning style as their way of learning followed by kinesthetic and auditory. And, it shows, too, female students are the most respondents who apply visual learning style into their learning process. Visual learning style becomes a preference for the most of students in learning due to an easier time processing and understanding information in any subject matter.